Hubungan Komorbid Hipertensi dengan Derajat Gejala Pasien COVID-19 - Inara Salsabilla; Kurnia Dwi Artanti; Santi Martini; Arief Hargono (Media Gizi Kesmas, 2023)
Background: COVID-19 in Indonesia has caused 142,173 deaths, East Java is one of the provinces and Surabaya is the city with the highest death rate in Indonesia. Hypertension and cardiovascular disease are the most common comorbidities found in COVID-19 patients. Objectives: The purpose of this study was to analyze the relationship of comorbid hypertension with the degree of symptoms of COVID-19 patients. Methods: The type of this research is quantitative analytic observational with the type of case control study design with a sample of 104 patients. The sampling technique used is simple random sampling. The data used in this study were the medical records of patients who were confirmed positive for COVID-19 at RSUD Dr. Soetomo Surabaya for the period March 2020 to September 2021. Data analysis uses the estimated value of the Odd Ratio (OR) Results: The results showed that the majority of elderly patients as many as 60 patients or 57.6% were male as many as 53 patients or 51%, had comorbid hypertension as many as 63 patients or 60.5% and the most common symptoms experienced by patients were colds and stones. . The results of the analysis showed that 34 patients or 72.5% had comorbid hypertension and had severe symptoms, 14 patients or 27.5% had no comorbidities and had moderate symptoms. Obtained p-value = 0.015> 0.05 so that comorbid hypertension has a significant relationship with the patient's symptoms. The estimated OR value is 2.744 (95% CI = 1.211-6215) which means that patients with hypertension have a 2.744 times greater chance of having severe symptoms than patients without hypertension..Conclusions: The conclusion of this study is that patients with hypertension have a 2.744 times greater chance of being symptomatic than patients without hypertension. Comorbid hypertension is a risk factor for severe symptoms of COVID-19 patients.